High-level programming for heterogeneous and hierarchical parallel systems. (November 2018) - García-Blas, Javier; Brown, Christopher
High-Level Heterogeneous and Hierarchical Parallel Systems (HLPGPU) aims to bring together researchers and practitioners to present new results and ongoing work on those aspects of high-level programming relevant, or specific to general-purpose computing on graphics processing units (GPGPUs) and new architectures. The 2016 HLPGPU symposium was an event co-located with the HiPEAC conference in Prague, Czech Republic. HLPGPU is targeted at high-level parallel techniques, including programming models, libraries and languages, algorithmic skeletons, refactoring tools and techniques for parallel patterns, tools and systems to aid parallel programming, heterogeneous computing, timing analysis and statistical performance models.